Review on Synthesis, Properties, and Performances of Polymer/ Metal Organic Framework (MOF) composites membranes for water filtration application - Ashfiya, Putri Sayyida; Khoerunnisa, Fitri; Nurhayati, Mita; Kadarohman, Asep; Sanjaya, Eli Hendrik; Hendrawan, Hendrawan; Sonjaya, Yaya; Aziz, Hafiz Aji; Annifah, Riri Uswatun; Iasya, Yurin Karunia Apsha Albaina (Jurnal Kartika Kimia, 2025)
Mixed matrix membranes (MMMs) have gained considerable attention as a cutting-edge filtration technology, leveraging the combined advantages of polymer and inorganic fillers. Metal-organic frameworks (MOFs), as a nanoporous materials, are regarded as highly effective fillers in MMM, significantly enhancing molecular separation efficiency. This article provides a comprehensive review of the synthesis, properties, and performance of polymer/MOFs-based MMMs. A comprehensive literature search was conducted using ScienceDirect and Google Scholar with keywords such as metal-organic framework, MMMs, polymers, filler, and membrane filtration. Polymer/MOFs-based MMMs are synthesized using techniques including in situ and layer-by-layer assembly methods. The MMMs exhibit porosity distribution ranges from57 to 78.3%, contact angle ranges from 45° to 75.27°. The MMMs have also demonstrated exceptional performance in water permeability and bovine serum albumin (BSA)/salts rejection reached up to 94.03 L/m2.h and 99.8%, respectively. These finding highlight the significant potential of polymer/MOFs-based MMMs for advanced water filtration application.